1986
DOI: 10.1002/ajmg.1320250525
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of a ketogenic diet in rett syndrome

Abstract: Seven girls (age 5 to 10 years) with Rett syndrome were investigated extensively. In 6 patients elevations of blood pyruvate were found. Blood lactate levels were marginally elevated. Two patients had variably elevated blood glucose levels. Metabolic studies were otherwise normal apart from minimally elevated blood ammonia levels in 3 of 5 patients tested, 2 of whom were on valproic acid. All 7 patients had anticonvulsant resistant seizures. multifocal spike wave discharges, and pseudo-periodic burst-suppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 9 publications
4
52
0
2
Order By: Relevance
“…Based on previous publications, medication use is largely based on regional prescribing practices rather than efficacy or adverse effects (Bao et al, 2013;Pintaudi et al, 2015). Although cases and retrospective studies document efficacy of specific medications in Rett syndrome, no systematic study has demonstrated superiority of a specific medication or class of medications to treat epilepsy in Rett syndrome (Haas et al, 1986;Kumandas et al, 2001;Goyal et al, 2004;Specchio et al, 2010). No specific medications are contraindicated in Rett syndrome; however, the issue of bone health is an important consideration when prescribing anti-seizure drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous publications, medication use is largely based on regional prescribing practices rather than efficacy or adverse effects (Bao et al, 2013;Pintaudi et al, 2015). Although cases and retrospective studies document efficacy of specific medications in Rett syndrome, no systematic study has demonstrated superiority of a specific medication or class of medications to treat epilepsy in Rett syndrome (Haas et al, 1986;Kumandas et al, 2001;Goyal et al, 2004;Specchio et al, 2010). No specific medications are contraindicated in Rett syndrome; however, the issue of bone health is an important consideration when prescribing anti-seizure drugs.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no longterm study using L-carnitine has been reported. Haas et al [1986] employed the ketogenic diet in an uncontrolled study of seven girls with RS. The diet composition provided fats in the form of medium chain triglycerides.…”
Section: L-carnitine Clinical Trialmentioning
confidence: 99%
“…Special interest has been given to various conditions associated with epilepsy including myoclonic astatic epilepsy, 5,9 infantile spasms, 7 Dravet syndrome, 10 atypical absences, 11 acquired epileptic aphasia, 12 tuberous sclerosis, 13 and Rett syndrome. 14,15 One study found slightly better results in generalized as opposed to focal epilepsy although this was not significant. 16 Lack of complex focal seizures was reported as a predictive factor for early, complete, and sustained response.…”
mentioning
confidence: 97%